Study of brain stem evoked audiometry in children under 10 years of age: a case series study - Suligavi, Shashidhar S.; Pawar, Shradha S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Brainstem evoked response audiometry (BERA) is a diagnostic tool which can be used to assess the early hearing loss and planning rehabilitative procedures. It is noninvasive and can be performed in uncooperative children. Methods: To evaluate the hearing threshold and find the incidence of hearing loss in infants and children under 10 years of age. Results: Totally, 55 patients under 10 years of age were included in the study. 15 children had normal hearing (27.27%) and 40 (72.72 %) were found to have sensorineural hearing loss. Amongst 40, 19 (47.5%) children were found in the age group of 1-5years. 14 (35%) were found to have profound hearing loss, 15 (37.5%) had severe, 8(20%) had moderate, 3 (7.5%) had mild hearing loss. Conclusions: Newborn screening is mandatory to identify hearing loss in the prelinguistic period to reduce the burden of handicap in the community. BERA should be carried out as a routine procedure to detect hearing impairment in high risk children and rehabilitative measures should be started as early as possible.